PENGARUH KETERAMPILAN, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) DI KABUPATEN BANGLI - Ni Kadek Dia Ardiyani; Gde Bayu Surya Parwita; Made Ika Prastyadewi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
The performance of employees in the company is a very important thing to be used as a benchmark for achievement in the company. The performance of employees in each company has different criteria according to the provisions of the company. The potential possessed by individuals also affects the level of performance produced by employees, where this potential can motivate employees to work optimally towards the company's operational activities, and can influence better employee work results. This study aims to analyze the influence of skills, work discipline, and work environment on employee performance at the Regional Drinking Water Company (PDAM) in Bangli Regency. The population in this study were all permanent employees at the Regional Drinking Water Company (PDAM) in Bangli Regency, totaling 98 people. The sample of this study was determined by saturated sampling technique, so that the number of samples was 98 people. The data analysis technique used is multiple linear regression analysis. The test results show that skills have a positive and significant effect on employee performance at the Regional Drinking Water Company (PDAM) in Bangli Regency. Work discipline has a positive and significant effect on employee performance at the Regional Drinking Water Company (PDAM) in Bangli Regency. The work environment has a positive and significant effect on employee performance at the Regional Drinking Water Company (PDAM) in Bangli Regency.